Pengaturan Lampu Lalu Lintas di Persimpangan Jalan Ahmad Yani Giant dengan Aplikasi Pewarnaan Teori Graf - Erna Lus Diana; Wahyuni Suryaningtyas; Endang Suprapti (Universitas Muhammadiyah Surabaya, 2016)
Traffic jam is problems faced by many cities in Indonesia. The density of highways has caused the congestion. One solution is to use a traffic light. The existence of traffic lights help to curb road users, but in many cases, the use of traffic lights is less than optimal. It is about the determination of flow which should be red or green and how long it takes for each stream. To overcome these problems, the coloring application used graph approach is as a point of scheduling problem resolution. The algorithm used is Welch-Powell. The case of a traffic light that occurs from several points in the city of Surabaya, one of which, is at the crossroads of Jalan Ahmad Yani Giant. Secondary data is from the Transportation Department of Surabaya including the results of the analysis of two-way road speeds using the Moving Car Observation of 2014, the average speed of vehicles in the city of Surabaya in 2010-2014, and the volume of vehicles on Jalan Ahmad Yani Surabaya. Congestion in Surabaya is caused by the increasing number or volume of vehicles in each year that is not balanced with the capacity of the road. Public awareness for the use of public transportation is also lacking. This is because the public transportation in the city of Surabaya has not fully met the standards and many are not fit for use so that people prefer to use private transport. Congestion is also caused by the lack of regulation of traffic police at the point of congestion during rush hour. From the above discussion, the result shows that the use of coloring application Graph Theory with Welch-Powell algorithm has improved the effectiveness of traffic lights which is seen from the total duration of the green and red light.